Attitudes and Interest in Technology-Based Treatment and the Remote Monitoring of Smoking among Adolescents and Emerging Adults. (8th October 2015) - McClure, Erin A.; Baker, Nathaniel L.; Carpenter, Matthew J.; Treiber, Frank A.; Gray, Kevin M.
Abstract : Introduction: Despite the public health relevance of smoking in adolescents and emerging adults, this group remains understudied and underserved. High technology utilisation among this group may be harnessed as a tool for better understanding of smoking, yet little is known regarding the acceptability of mobile health (mHealth) integration. Methods: Participants (ages 14–21 years) enrolled in a smoking cessation clinical trial provided feedback on their technology utilisation, perceptions, and attitudes; and interest in remote monitoring for smoking. Characteristics that predicted greater technology acceptability for smoking treatment were also explored. Results: Participants ( N = 87) averaged 19 years old and were mostly male (67%). Technology utilisation was high for smart phone ownership (93%), Internet use (98%), and social media use (94%). Despite this, only one-third of participants had ever searched the Internet for cessation tips or counselling (33%). Participants showed interest in mHealth-enabled treatment (48%) and felt that it could be somewhat helpful (83%). Heavier smokers had more favourable attitudes toward technology-based treatment, as did those with smartphones and unlimited data. Conclusions: Our results demonstrate high technology utilisation, favourable attitudes towards technology, and minimal concerns. Technology integration among this population should be pursued, though in a tailored fashion, to accomplish the goal of providing maximally effective, just-in-time interventions.